The Association Between Medical Factors During Pregnancy and Cesarean Section in Bandar Abbas-Prospective Cohort - Fatemeh Sharifnia; Mohsen Ostadghaderi; Hossein Moameri (Fasa University of Medical Sciences, 2020)
Background & Objectives: Cesarean section rates have increased significantly over the past decade. This increase has not been clinically justified. The objective of this study was to investigate the effect of medical factors on the type of delivery. Materials & Methods: This prospective cohort study was done on 200 pregnant mothers. The main exposure in this study was the medical reasons for cesarean section and the main outcome of cesarean delivery. The relative risk index was calculated using the Cox regression model. Results: Of the 196 pregnant women remained in the study, 40.31% had Cesarean section. Compared to non-medical factors, the risk of Cesarean section was higher (Relative Risk = 4.64) in mothers with medical factors. Also, the risk of elective Cesarean section was higher in mothers with medical factors (Relative Risk = 2.34). On the other hand, the risk of Cesarean section and elective Cesarean section was and higher in mothers with previous abortion (Relative Risk = 2.11) and hard labor (Relative Risk = 3.25), respectively. However, there was a significant relationship between maternal mental disorder during pregnancy and Cesarean section delivery (Relative Risk = 1.49). Conclusion: Based on these results, there is an association between medical factors and type of delivery. Therefore, maternal preventable or controllable medical problems during pregnancy requires more attention.